Research progress and understanding of fracturing fractures in horizontal wells of marine shale in Sichuan Basin - YANG Zhaozhong, YUAN Jianfeng, ZHANG Jingqiang, LI Xiaogang, ZHU Jingyi, HE Jiangang (Youqicang pingjia yu kaifa)
The rapid development of shale gas, a clean and low-carbon unconventional natural gas, plays a key role in supporting China’s goals for achieving a carbon peak and carbon neutrality. Over the past decade, China has made significant strides in the theoretical and technical aspects of shale gas fracturing, progressing from non-existence to existence and evolving from followers to partially leading the field. This paper discusses three critical aspects of the shale gas fracturing process: fracture layout, fracture creation, and support fracture, yielding several key insights: ① The primary objectives in optimizing the characteristics of the fracture network are to maximize reservoir modification volume and fracture complexity. This maximization is crucial for enhancing the shale gas production capacity. ② During the fracturing process, it is essential to ensure uniform fracture initiation across each cluster. However, due to the non-homogeneity of the ground stress field and the presence of structural weak surfaces such as natural fractures, inter-cluster collusion or overlap of fractured fractures often occurs. This results in the actual fracture seam spacing being unequal to the planned cluster spacing. ③ Under conditions of close cutting and strong sand addition, the applicability of limit flow restriction fracturing is limited. The scientific challenges related to temporary plugging at the fracture mouth, temporary plugging within the fracture, and sand placement in narrow bifurcation seams remain unresolved. These challenges involve complex liquid-solid two-phase flow dynamics. ④ For fractures containing proppant, it is necessary to determine the inflow capacity demand and distribution mode based on the reservoir’s capacity or production demands. Subsequently, optimizing the proppant parameters and the sand placement process is crucial. The paper concludes that ongoing enhancement in theoretical research and process technology related to the fracturing transformation of deep and ultra-deep shale reservoirs is essential. It is imperative to refine, accurately design, and differentially set the fracturing construction parameters, elucidate the transport mechanism and distribution mode of proppant in complex fracture networks, and optimize fracture conductivity comprehensively. The research findings presented here are of significant reference value for the development of deep to ultra-deep shale gas in China, aiming to achieve cost reduction, quality improvement, and efficiency enhancement.